1976
DOI: 10.1295/polymj.8.247
|View full text |Cite
|
Sign up to set email alerts
|

Hypochromic Effects in UV Spectra of Polymers in Solution

Abstract: ABSTRACT:The hypochromic effect in the UV spectra of polystyrene and styrene copolymers in solution was investigated in detail. For this purpose, isotactic and syndiotactic-rich polystyrenes as well as their dimer model compounds, 2,4-diphenylpentanes, and styrene-methyl methacrylate copolymers were prepared. UV absorption measurements were carried out in dioxane and tetrahydrofuran at various temperatures. The extinction coefficients of phenyl rings depended not only on the solvent and the temperature but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…These deviations have been attributed to the microstructure of the polymer chains (3,4,8,10, I I) and in some cases to the conformation of the molecules in solution (2, 6, 9). Vala and Rice (2) observed that the extinction coefficient of isotactic polystyrene at certain wavelengths is smaller than the corresponding extinction coefficients for atactic polystyrene.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These deviations have been attributed to the microstructure of the polymer chains (3,4,8,10, I I) and in some cases to the conformation of the molecules in solution (2, 6, 9). Vala and Rice (2) observed that the extinction coefficient of isotactic polystyrene at certain wavelengths is smaller than the corresponding extinction coefficients for atactic polystyrene.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also concluded that the response of the uv detector appears to be a function of the length of the styrene sequences. Stutzel et al (8) investigated SMMA copolymers in THF and dioxane solutions. From their analysis using styrene dimers they concluded that the hypochromic effects are probably not due to differences in conformation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-association of the dye molecules is often accompanied by a hypochromic effect in UVVis spectra. [10][11][12][13][14][15] Spectra of mono-NBD derivatives of OPAs are similar to the known NBDamines 5 and contain two main bands near 350 and 500 nm (Table 1, Figure 1) irrespective of pH values. A decrease of absorbance at 500 nm was observed for NBD-N2H at pH 10 only.…”
Section: Introductionmentioning
confidence: 80%
“…5 The UV spectra of the random copolymers might become similar to those for the alternating copolymers when the styrene content in the random copolymers is lower than 10%. The ratio of the molar absorption coefficients for a random copolymer having 20 mol% styrene and PS at 269.6 nm5 was 0.690; in this work it was 0.842.…”
Section: Samplesmentioning
confidence: 94%